FTIR Spectral and Statistical Studies on Alcoholic and Non-Alcoholic Blood Samples - Chandramalar, I. Monica; Sankari, G.; Gunasekaran, S.; Venkatraman, S. (Asian Journal of Chemistry, 2016)
This work focuses on Fourier transform infrared (FTIR) spectroscopic technique which is employed to study the spectral differences between the non-alcoholic and alcoholic blood samples. The studies conducted on the blood samples of alcoholic patients and the results were compared with the non-alcoholic patients using FTIR spectroscopic technique combined with statistical analysis. It is observed that the general shape of the spectra is the same but there is considerable change in the absorption of the characteristic peaks. As a measure to characterize the non-alcoholic and alcoholic blood, the intensity ratio calculation have been carried out among some of the specific absorption peaks for both non-alcoholic and alcoholic samples. It is found that the values are different in both the samples. Thus the role of FTIR spectroscopy in the clinical analysis of blood samples has been established both qualitatively and quantitatively. Statistical analysis is performed to find whether the absorption ratios differ in the healthy and diseased groups employing analysis of variance (ANOVA) and independent t-test.